Defining the Efficacy and Safety of Phosphodiesterase Type 5 Inhibitors with Tamsulosin for the Treatment of Lower Urinary Tract Symptoms Secondary to Benign Prostatic Hyperplasia with or without Erectile Dysfunction: A Network Meta-Analysis. (27th March 2020) - Ma, Chengquan; Zhang, Jianzhong; Cai, Zhonglin; Xiong, Jian; Li, Hongjun
Abstract : Purpose . The purpose of this study was to compare the relative safety and efficacy of different types of phosphodiesterase type 5 inhibitors (PDE5-Is) with tamsulosin for the treatment of lower urinary tract symptoms (LUTS) secondary to benign prostate hyperplasia (BPH) (BPH-LUTS) with or without erectile dysfunction (ED). Methods . We use the Stata version 13.0 to conduct the network meta-analysis (NMA) with a random effects model of the Bayesian framework. The International Prostate Symptom Score (IPSS), Maximum Urinary Flow Fate (Q max ), International Index of Erectile Function (IIEF), and their credible intervals (CI) were used to compare the efficacy and safety of every medical intervention, including sildenafil plus tamsulosin, tadalafil plus tamsulosin, and vardenafil plus tamsulosin. Results . Seven RCTs including 531 participants with seven interventions were analyzed. The results of NMA SUCRA showed that compared with different doses or types of PDE5-Is combined with tamsulosin (0.4 mg qd), the sildenafil (25 mg qd) combined with tamsulosin (0.4 mg qd) group had the greatest probabilities of being the best in the achievement of improving IIEF. The sildenafil (25 mg 4 days per week) combined with tamsulosin (0.4 mg qd) group had the greatest probabilities of being the best in the achievement of improving Q max, whereas sildenafil (25 mg qd) combined with tamsulosin (0.4 mg qd) ranked the best for the safety outcomes. Conclusions . This meta-analysis indicates that sildenafil combined with tamsulosin is the best effective and tolerated treatment option for BPH-LUTS with or without ED. Further RCTs are strongly required to provide more direct evidence.